Pengaruh Rasio Likuiditas dan Ukuran Perusahaan Terhadap Financial Distress pada Perusahaan Manufaktur (Sub Sektor Food And Beverage ) Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Dini Arifian (E-Journal Studia Manajemen, 2021)
Financial distress is a situation when a company is unable to fulfill its obligations. This happens as an early sign before the worst thing finally happens, namely bankruptcy. This study aims to determine the effect of liquidity ratios and company size on financial distress either partially or simultaneously in food and beverage companies listed on the Indonesian stock exchange for the 2017-2020 period. The method used in this research is descriptive analysis with a quantitative approach. The total population in this study were 30 companies and after selecting the sample using purposive sampling technique, 9 companies were obtained that would be used as samples in this study. The type of data used in this study is secondary data. The data analysis model used in this study is using the prerequisite test for data analysis which includes: normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The hypothesis test used in this study includes: multiple linear regression analysis, correlation analysis, coefficient of determination, t test and f test. Based on the results of the multiple linear regression test, the Liquidity Ratio to Financial Distress obtained a value of 0.284 and the Company Size variable to stock prices obtained a value of 0.052. Based on the results of the correlation test, the value of Liquidity on Financial Distress is 0.516 and Company Size on Financial Distress is 0.256. Based on the hajj determination test, the R Square value was 0.325. Based on the results of the t test that has been done, the Liquidity Ratio variable has a significant effect on Financial Distress. While the Firm Size variable has an effect on Financial Distress. In this study, the significant level was taken = 5% or = 0.05, there was an Fcount value of 9.414 and an Ftable value of 3.28. These results show the value of Fcount (9.414) > Ftable (3.28) with a significance value of 0.000 <0.05. This means that together the Liquidity Ratio and Company size have a significant effect on Financial Distress Based on the data analysis, it can be concluded simultaneously (together) that the Liquidity Ratio and Company Size have an effect on Financial Distress.